Capacity Constraints and Public Financial Management in Small Pacific Island Countries. Issue 3 (14th April 2015) - Haque, Tobias Akhtar; Knight, David; Jayasuriya, Dinuk
Abstract: Sound public financial management is a key concern of Pacific island country governments and their development partners. Public Expenditure and Financial Accountability assessments have become a ubiquitous tool for assessing public financial management performance in the region. This paper summarizes Pacific island country performance using global data and identifies a relationship between small population size and lower scores in Public Expenditure and Financial Accountability assessments. This relationship reflects capacity constraints to successful implementation of capacity‐intensive public financial management functions measured in such assessments. The analysis suggests that high scores may be an unrealistic and inappropriate goal for Pacific governments and development partners. Greater account should be taken of population‐related capacity constraints when designing and implementing public financial management reforms. Scarce capacity should be prioritized towards binding constraints to service delivery and macroeconomic management, rather than dispersed in attempts to improve assessment scores through adopting capacity‐intensive 'best‐practice' systems.